The Intersection of English Theatre and Environmentalism: A Study of Eco-Theatre and its Impact - Rihab Arif Abdulsahib, Lecturer (lark, 2026)
In this paper, I take up the relationship of English theatre and environmentalism in eco-theatre as an art form of environmental awareness. Drawing on insights gained from ecocriticsm, performance theory, and eco-aesthetics, the book explores the ways in which English playwrights and directors such as CarylChurchill, Duncan Macmillan and Katie Mitchell are responding to environmental devastation, climate change and sustainability. This article is tracing the history of theatres in England, from the pastoral allegoricism of the drama played by Shakespeare, to the environmental-related issues being acted up, to some eco-performances where science and activism interweave. Using The Skriker (1994), 2071 (2014) and Ten Billion (2012) as examples the thesis demonstrates how eco-theatre transforms space, aesthetics and audience engagement to generate eco-awareness. Ultimately the eco-theatre is a combination between a form of cultural critique and environmental activism using empathy, education and a sense of shared responsibility. Thus, the English language a) operates, as it has done so for thousands of years, as an expression of the ecology transformation, but also b) serves as a force for promoting a sustainable cultural ecology.